Incidencia económica y social del servicio telefónico móvil en el nivel de ingresos de los habitantes del cantón Quevedo, año 2013. - Salazar Solórzano, Francisco Wladimir (2015)
To carry out the proposed research regarding the "economic and social impact of mobile phone service in the income of the inhabitants of Canton Quevedo, 2013" the following specific objectives were raised; investigate the supply of mobile telephone service and growth rates nationwide, identify the level of consumption and social factors that lead people to use mobile phones in Canton Quevedo, establish the advantages and disadvantages caused by the use of mobile phone in the inhabitants of Canton Quevedo and determine the economic impact of mobile phone in the level of income earned by residents of Canton Quevedo. Information search is performed by the application of research methodology, where they intervened methods, types and techniques, also sample survey of 383 inhabitants was obtained. Analysis of the data was accomplished as follows; mobile telephony in Ecuador in the last ten years has been growing at a rapid pace going since 2002 with 12.33% in 2008 to 84.70% until the year 2014 a total of 113 , 32% in terms of business development. Among the social factors found that 56.92% of respondents have at least one cell and 37.34% up to two, the 50.39% use the mobile for work, 30% of necessity to communicate with family , friends, etc. On the other hand the 59.79% spend between $ 10 to $ 20 per week in mobile telephony. The advantages of having the service of cellular operators are; fast communication, development of economic activities, problem solving, improving academic performance and interpersonal relationships, while the disadvantages are; increased costs, high degree of dependence, disconnection from reality, little physical activity. The average monthly income earned by the 37.34% of the…